1995
DOI: 10.1007/bf00232656
|View full text |Cite
|
Sign up to set email alerts
|

Morphotypes of friable embryogenic maize callus

Abstract: Friable, embryogenic callus cultures of maize are normally maintained as a heterogeneous mixture of various morphotypes in different stages of development (Fransz and Schel 1991). With stringent selection during subculture, three Type II callus morphotypes have been enriched and maintained. Cultured tissue segments from the three morphotypes referred to as "pre-embryogenic", "early embryogenic", and "late embryogenic" were analyzed using light and scanning electron microscopy. The results suggest a development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…Vain et al (1989) demonstrated that 5-10 mg l -1 AgNO 3 enhanced the induction of type-II callus from immature embryos of the maize line A188. A positive response was observed within a range of 1.8-18 mg l -1 for inbred line B73 and its derivatives (Songstad et al 1991;Welter et al 1995). Even though a few tropical maize genotypes have shown the capacity to produce type-II callus, this was improved by the addition of 15 mg l -1 AgNO 3 (Bohorova et al 1995;Carvalho et al 1997).…”
Section: Callus Inductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Vain et al (1989) demonstrated that 5-10 mg l -1 AgNO 3 enhanced the induction of type-II callus from immature embryos of the maize line A188. A positive response was observed within a range of 1.8-18 mg l -1 for inbred line B73 and its derivatives (Songstad et al 1991;Welter et al 1995). Even though a few tropical maize genotypes have shown the capacity to produce type-II callus, this was improved by the addition of 15 mg l -1 AgNO 3 (Bohorova et al 1995;Carvalho et al 1997).…”
Section: Callus Inductionmentioning
confidence: 90%
“…Induction and maintenance of embryogenic-callus from immature embryos were evaluated based on the previously described N6C1 medium (Bohorova et al 1995), which consisted of N6 basal medium (Chu et al 1975) supplemented with 200 mg l -1 casein hydrolysate, 2.302 mg l -1 L-proline, 3% sucrose and 2 mg l -1 Dicamba; addition of three doses of AgNO 3 at 10 (N6C1-10), 15 (N6C1-15) and 20 mg l -1 (N6C1-20) into the base N6C1 medium, were evaluated for its ability to induce embryogenic type-II callus from the embryo-scutellum as has already been demonstrated on several tropical maize lines (Vain et al 1989;Welter et al 1995;Carvalho et al 1997). For callus initiation and maintenance, immature embryos were cultured oriented with the embryo-axis side in contact with the medium (scutellum side up) and incubated in the darkness at 27掳C; embryogenic tissue was subcultured to fresh medium every 20 days.…”
Section: Induction and Maintenance Of Calli And Plant Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Only the Type II embryogenic callus (EC) is highly regenerative (Burris et al 2009). This phenomenon was also found on other monocots, such as maize (Armstrong and Green 1985;Vasil and Vasil 1994;Welter et al 1995), rice (Rueb et al 1994), sugarcane (Guiderdoni and Demarly 1988), wheat (Parmar et al 2012), and various non-food grasses (Lu and Vasil 1981;Zhang et al 2007;Li and Qu 2011). In general, two types of calluses had been classified and described depending on color, regeneration ability and texture.…”
mentioning
confidence: 93%
“…The morphology of callus has been reported and described in the important agronomic monocot crops such as maize [8][9][10][11][12][13][14], rice [15][16][17], sorghum [18], sugarcane [19], wheat [20], and various nonfood grasses [21][22][23][24][25][26]. Type I callus is the typical and most prevalent callus formed in monocot species.…”
Section: Introductionmentioning
confidence: 99%